2016
DOI: 10.1212/wnl.0000000000002671
|View full text |Cite
|
Sign up to set email alerts
|

Depression in amyotrophic lateral sclerosis

Abstract: Objective: To examine the relative risk of depression among patients with amyotrophic lateral sclerosis (ALS), both in terms of depression diagnosis and use of antidepressant drugs, before and after diagnosis. Methods:We conducted a nested case-control study including 1,752 patients with ALS diagnosed from July 2005 to December 2010 and 8,760 controls based on the Swedish national health and population registers, to assess the associations of depression diagnosis and use of antidepressant drugs with a subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 30 publications
6
69
0
2
Order By: Relevance
“…Depression is the most common psychiatric symptom and occurs in 33–70% of patients with Huntington disease [25]. The prevalence of antidepressant use was reported up to 38% among patients with ALS [26]. In patients of Alzheimer’ disease, depression is found to be an omnibus prevalence of 32% (16% in population-based Alzheimer’ disease studies, and 44.3% in hospital-based studies) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is the most common psychiatric symptom and occurs in 33–70% of patients with Huntington disease [25]. The prevalence of antidepressant use was reported up to 38% among patients with ALS [26]. In patients of Alzheimer’ disease, depression is found to be an omnibus prevalence of 32% (16% in population-based Alzheimer’ disease studies, and 44.3% in hospital-based studies) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Both databases have individual strengths and weaknesses, and both are considered well validated and well recognised for pharmacoepidemiologic research with numerous publications. (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Regarding the first issue raised by Potteg ard et al, i.e. the definition of pregabalin exposure in our study, in a 2011 presentation, Thompson et al (16) demonstrated a very high correlation between prescribing recorded in THIN data and drug dispensing in England.…”
Section: To the Editormentioning
confidence: 49%
“…В отечественной лите-ратуре имеются указания на то, что такие депрессии явля-ются преимущественно нетяжелыми (нозогенные), не имеют тенденции к эндогенизации и характеризуются преобладанием тревожных симптомов [23]. Депрессии отмечаются на разных этапах заболевания: они могут предшествовать появлению первых моторных симптомов, формироваться на диагностическом этапе, а также разви-ваться после достоверного установления диагноза [35]. На позднем этапе заболевания клиническая картина депрес-сии обычно усложняется за счет присоединения псевдо-бульбарных симптомов (насильственный смех и плач) [36].…”
Section: постинсультные депрессииunclassified